SOSIALISASI KEOLAHRAGAAN DENGAN MASSAGE DAN FISIOTERAPI OLAHRAGA SEPAKBOLA DI SMPN 1 SIDAMANIK - Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Miracle Noel Christian Pancaribuan (Yayasan Nusantara Hasana Berdikari, 2025)
The primary aim is to enhance the understanding and skills of students and coaches in post-exercise physical care. This socialization is considered important to prevent injuries and optimize recovery from intensive training, given that many students experience muscle soreness. The methods used include lectures, demonstrations of techniques, hands-on practice, and interactive discussions. The activities are organized into three stages: preparation, implementation, and evaluation. Over two days, the program seeks to provide practical knowledge about massage and physiotherapy, with the expectation of reducing injuries and increasing awareness of the importance of physical care in sports.